Resonating with Postmodern Community Empowerment and Localization Initiatives - Manimtim, Herminia (Social Sciences and Development Review, 2015)
For more than two centuries now, the globalized mainstream economy has ruled the world. Realities and studies reveal that despite unprecedented wealth creation of the global economic system and the pledge of 189 country signatories in the Millennium Development Declaration to eradicate poverty, inequities and hunger prevail particularly in developing nations. As offshoot of the failure of the mainstream system to trickle down progress and equity, the grassroots, advocacy groups, development practitioners and scholars have been pursuing deliberate actions in line with paradigms such as localization, community economic development and direct social well-being. The aim is to spur responsive and sustainable development from below.